2021
DOI: 10.1177/10105395211014648
|View full text |Cite
|
Sign up to set email alerts
|

Caste Exclusion and Health Discrimination in South Asia: A Systematic Review

Abstract: The caste system is social stratification system that has been used over the last 3 millennia. This review aims to investigate caste-based inequity in health care utilization in South Asia, particularly focusing those at the bottom of the caste hierarchy, commonly known as Dalit communities. A systematic methodology was followed; key databases (including CINAHL, Medline, SocINDEX, PubMed, Nepjol, JSTOR, and ASSIA) were searched for relevant articles published before October 2019, using comprehensive search str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Inequality in child nutrition between scheduled caste and the remaining population was also reported by a study conducted in India [ 4 ], which found that the gap was both due to differences in the distribution of level of predictors (wealth, education, use of health services) and effect of the predictors. In Nepal and India, caste-based discrimination put Dalit and minority groups in a disadvantaged position which is manifested in the differential health outcomes between groups [ 4 , 48 ]. In addition, between-group differences in the effect of the number of under-five children in household and the age of mother jointly accounted for about 56% of the gap due to coefficient effects.…”
Section: Discussionmentioning
confidence: 99%
“…Inequality in child nutrition between scheduled caste and the remaining population was also reported by a study conducted in India [ 4 ], which found that the gap was both due to differences in the distribution of level of predictors (wealth, education, use of health services) and effect of the predictors. In Nepal and India, caste-based discrimination put Dalit and minority groups in a disadvantaged position which is manifested in the differential health outcomes between groups [ 4 , 48 ]. In addition, between-group differences in the effect of the number of under-five children in household and the age of mother jointly accounted for about 56% of the gap due to coefficient effects.…”
Section: Discussionmentioning
confidence: 99%
“…Not only in Indian society, but caste also shows its presence in other South Asian countries (Thapa et al, 2021), making the caste system a global issue. Researchers have also revealed the prominence of caste discrimination in the UK (Dhanda, 2017;Gorringe et al, 2017), Kuwait and the UAE (Leonard, 2005).…”
Section: The Caste Systemmentioning
confidence: 99%
“…The hierarchy of caste and gender makes lower caste women face ''double discrimination'' (Paik, 2014) and suffer from double the effects of marginalisation. Dalit women are doubly disadvantaged due to their low-caste status and the lower status of women in Hindu society, also known as the ''Dalit among Dalits'' (Thapa et al, 2021). Research suggests that discrimination and violence continue based on women's intersecting caste and gender identities (Pal, 2014(Pal, , 2015.…”
Section: Caste Gender and Well-beingmentioning
confidence: 99%
“…Defined benefit Malfeasance... Liability Malfeasance.... Correlativperso Vicarious Competence is a term used to describe when someone else is responsible for another person Offenses (for example, purposefully striking a person), irresponsible torts (for example, hit a pedestrian by refusal to maintain traffic regulations), nor mandatory reporting torts (for illustration, hit a pedestrian by failing to follow traffic rules) are the three types of law of tort [18][19][20][21][22][23][24][25][26].…”
Section: Diagnosismentioning
confidence: 99%